Autologous and allogeneic stem cell transplantation in multiple myeloma - Goldschmidt, Hartmut; Egerer, Gerlinde; Ho, Anthony Dick (Bone marrow transplantation, 2000)
Multiple myeloma is still an incurable disease. The standard conventional chemotherapy comprises melphalan and prednisone (MP). Combination chemotherapy regimens could not improve the median survival of 36 months observed with MP. In the French IFM90 study, HD therapy with TBI plus melphalan 140 mg/m2 was shown to prolong overall survival and progression-free survival compared to conventional treatment. Nonetheless, most patients eventually succumb due to disease progression. Allogeneic transplantation may induce long-term remissions and even cure, but is hampered by a high transplantation-related mortality (TRM). Currently, efforts are made to reduce this TRM and to evaluate the graft-versus-myeloma effect.